An Instructional Video to Improve Teaching Techniques and Learning in the Operating Room - Eric Sokol; William Metheny; Renee Ward (Association of American Medical Colleges, 2009)
Abstract Few physicians are given formal training in educational techniques, which is unfortunate because formal instruction on teaching has been shown to be effective and can improve the overall quality of the clerkship. Based on the premise that most physicians receive little formal training on how to teach in the operating room, this video was developed to demonstrate a stepwise approach to teaching these skills. This resource is a 15-minute, professional-quality instructional video which follows the steps described in the accompanying detailed teaching outline. The video is divided into three segments that describe techniques for early involvement, continuous participation, and post-operative duties of the learner assistant. It provides the surgeon with concrete examples of how to engage and make the surgical assistant accountable for learning. The surgeon in this video explains the roles and responsibilities of the assistant and demonstrates methods to engage the assistant in the pre-operative phase, with chart review and anatomical drawings; introductions to the team and patient; and positioning the patient. In the operative phase the surgeon asks questions about the disease process, points out anatomy, and demonstrates surgical techniques. In the post-operative phase, the assistant "dictates" the operative reports, writes "orders," and rounds on the patient under the surgeon's supervision. After exposing OB/GYN residents to this video, we observed an overall improvement in the medical students' ratings of teaching in their clerkship evaluations compared to baseline ratings. This video offers a detailed set of skills that the surgeon can readily use to engage the surgical learning assistant. Often, this assistant is not integrated into the surgical team or given specific learning responsibilities so they miss out on most of the learning opportunities the case provides. This video teaches the surgeon how to make the student feel like a valued and respected member of the surgical team, thus enhancing the student's learning opportunities. We found that if the video is shown only once at the beginning of the year, some of the learners will forget the effective teaching tips by the time they start their surgical rotations. The effectiveness of this video is therefore maximized if it is shown to each new group of residents prior to starting their surgical rotations. The impact of the video on teaching will also be maximized if the teachers have an opportunity to practice the steps described in the video, such as in small groups with a teacher, student, and observer. This practice allows them to integrate and upgrade their teaching practices with these skills.